Prophylactic Left Atrial Appendage Exclusion in Cardiac Surgery Patients With Elevated CHA2DS2-VASc Score: Results of the Randomized ATLAS Trial. Issue 6 (November 2022) - Gerdisch, Marc W.; Garrett, H. Edward; Mumtaz, Mubashir A.; Grehan, John F.; Castillo-Sang, Mario; Miller, Jeffrey S.; Zorn, George L.; Gall, Stanley A.; Johnkoski, John A.; Ramlawi, Basel
Objective: Patients with elevated CHA2 DS2 -VASc scores are at high risk for atrial fibrillation (AF) and thromboembolic events (TE) after cardiac surgery. Left atrial appendage exclusion (LAAE) is a permanent, continuous approach to stroke prevention in AF, overcoming limitations of oral anticoagulation (OAC). We report ATLAS trial results focused on LAAE technical success and perioperative safety and TE rates with and without LAAE in cardiac surgery patients who developed postoperative AF (POAF). Methods: ATLAS (NCT02701062) was a prospective, multicenter, feasibility trial. Patients age ≥18 years, undergoing structural heart procedure, with no preoperative AF, CHA2 DS2 -VASc ≥2, and HAS-BLED ≥2 were randomized 2:1 to LAAE or no LAAE. Patients who developed POAF and/or received LAAE were followed for 1 year. LAAE was evaluated with intraoperative transesophageal echocardiography. Results: A total of 562 patients were randomized to LAAE ( n = 376) or no LAAE ( n = 186). Mean CHA2 DS2 -VASc (3.4 vs 3.4) and HAS-BLED (2.8 vs 2.9) scores were similar for LAAE and no LAAE groups. LAAE success (no flow nor residual stump >10 mm) was 99%. One LAAE-related serious adverse event (0.27%) occurred and was resolved without sequelae. There were 44.3% of patients who developed POAF. Through 1 year, 3.4% of LAAE patients and 5.6% of no LAAE patients had TE. OAC was used by 32.5% of POAF patients. Bleeding was higher with OAC than without (16.1% vs 5.4%, P = 0.008). Conclusions: ATLAS demonstrated a high rate of successful LAAE with low LAAE-related serious adverse events in cardiac surgery patients. Study results should be considered in future trial design to further evaluate prophylactic LAAE for stroke prevention in cardiac surgery patients with elevated stroke risk.